Efficacy and safety of anterior vaginal prolapse treatment using single incision repair system: Multicentric study - Marzio Angelo Zullo; Michele Carlo Schiavi; Paolo Luffarelli; Gianluca Bracco; Alessandro Iuliano; Debora Grilli; Francesco Esperto; Mauro Cervigni (Elsevier, 2022)
Objective: Up to 80% of all POP surgical procedures are due to anterior vaginal wall prolapse.The aim of this study is to evaluate the efficacy and safety of transvaginal anterior mesh for POP surgical repair. Materials and methods: 153 consecutive patients with symptomatic or recurrent anterior vaginal prolapse undergoing surgical single-incision mesh (Calistar S) were prospectively enrolled in the study. Preoperative evaluation was performed collecting urogynecological history and performing a clinical exam, 3-day voiding diary and urodynamic testing. All incontinent patients completed the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF). Operative time, blood loss, perioperative and postoperative complications were prospectively recorded. Postoperative follow-up was scheduled at 1, 6, and 12 months with a urogynecological interview and examination.Success rate was assessed at 1, 6 and 12 months postoperatively. Results: The median follow-up was 16.4 months. None of patients had intraoperative complications. Eight patients (5%) required surgical intervention for complications (5 patients (3%) for haematoma and 3 (2%) for vaginal erosion). At 12 months of follow up 130 out of 140 patients (93%) gained the subjective cure criterion, while 129 out of 140 patients (92%) obtained the objective cure criterion. Eleven (7.8%) patients experienced stage 2 or higher prolapse recurrence and three of them with a stage ≥3 underwent reintervention. No significant differences were recorded in primary outcome at 1, 6 or 12 months postoperatively. Conclusions: Anterior compartment prolapse repair by Calistar S (single-incision vaginal mesh) is an effective and safe procedure without significant complications.